Identification of Theileria mutans-specific antigen for use in antibody and antigen detection ELISA - Katende, J.M.; Goddeeris, M.; Morzaria, S.P.; Nkonge, C.G. (Wiley, 1990)
Summary Purified piroplasms of Theileria mutans were used to immunize BALB/c mice to generate monoclonal antibodies (MoAbs). The MoAbs recognized an antigen of a relative molecular mass of 32 kDa in Western blots. This antigen was also recognized by sera from cattle which had recovered naturally from experimental tick‐transmission or infections induced by the blood stages of T. mutans. The MoAbs did not react, in indirect immunofluorescence or enzyme‐linked immunosorbent assays (ELISA), with the common haemoparasites of cattle, namely, T. parva, T. annulata, Babesia bigemina, B. bovis, Anaplasma marginale, Trypanosoma congolense, T. vivax or T. brucei. An antigen capture ELISA was established with two of the MoAbs which recognized different epitopes on the 32 kDa molecule. Using this test it was possible to detect circulating antigens or immune complexes in sera collected from cattle during the acute or chronic phases of infection. When the purified 32 kDa protein was used as antigen in a micro‐ELISA to detect circulating antibodies in both experimental and field cattle sera, it was found that the titres of antibodies ranged between 1:20 and 1:10 240. Results of this study indicate that the antigen and immune complex capture assays and the antibody detection ELISA can be complementary in the immunodiagnosis of acute and chronic T. mutans infections. Moreover, the tests are useful in the differential diagnosis of the disease and for epidemiological studies.